The Political Economy of Village Sanitation in South India : Capture or Poor Information ? - Ban, Radu; Das Gupta, Monica; Rao, Vijayendra (Washington, DC: World Bank, 2012)
Despite efforts to mandate and finance local governments' provision of environmental sanitation services, outcomes remain poor in the villages surveyed in the four South Indian states. The analysis indicates some key issues that appear to hinder improvements in sanitation. Local politicians tend to capture sanitary infrastructure and cleaning services for themselves, while also keeping major village roads reasonably well-served. Their decisions suggest, however, that they neither understand the health benefits of sanitation, nor the negative externalities to their own health if surrounding areas are poorly served. Our findings suggest that improving sanitary outcomes requires disseminating information on the public goods nature of their health benefits, as well as on the local government's responsibilities. It also requires putting public health regulations in place, along with measures to enable accountability in service provision.